Are Doctors Easy Targets for Cyber Frauds? - Sadananda B Naik; Sangram Biradar (Bengal Physician Journal)
Doctors seem to be a soft target for the scamsters for cyber frauds. We are otherwise known for our intelligence and shrewdness, fall prey to these cyber criminals with ease. This is a short write-up on this very problem.